School Adjustment among South Korean Students Studying in Bengaluru - Victor, Samson R.; song, jinyoung (Advances in Social Sciences Research Journal, 2015)
This study examines the school adjustment among South Korean students studying in Bengaluru, India. The method of study adopted is survey for the school adjustment and the target group is106 Korean students ranging from grade 5 to 12 studying in public and international school in Bengaluru. To identify their school adjustment, five aspects which may influence to school adjustment are introduced: Gender, Grade, Type ofSchool, Parents who live with the students or not and residing period.The findings are most (69.8%) of Korean students show a medium level of school adjustment and girls, international school students and students who reside longer show better school adjustment rather than boys, public school students and students who have short period of residing in Bengaluru. Keywords:studying abroad, school adjustment, Korean educational system, Indian educational system.